The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/pr300020p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of EFEMP2 as a Serum Biomarker for the Early Detection of Colorectal Cancer with Lectin Affinity Capture Assisted Secretome Analysis of Cultured Fresh Tissues

Abstract: Early diagnosis plays a decisive role in the outcome of colorectal cancer (CRC) therapy. The ex vivo culture of fresh CRC tissues and paired normal colorectal tissues provides a feasible way to explore potential serum biomarkers for CRC early detection under near-physiological conditions. In the present work, we applied a lectin affinity based approach to enrich and increase the detection number of secreted proteins in the conditioned media of cultured tissues. The captured proteins were then analyzed by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 70 publications
1
48
0
Order By: Relevance
“…In addition to these concordances with clinical gene expression data, our proteomics-based discovery pipeline identified other proteins that are potential serological biomarkers for colorectal cancer patients: a recent study by Yao and colleagues [28] identified EFEMP2 (EGF-containing fibulin-like extracellular matrix protein 2 or Fibulin 4) and thrombospondin 2 (THBS2) as a potential biomarkers detected in the serum of colorectal cancer patients. In accord with these data, we detected both EFEMP2 and THBS2 in both primary and secondary colon tumors but not in normal tissues.…”
Section: Resultsmentioning
confidence: 80%
“…In addition to these concordances with clinical gene expression data, our proteomics-based discovery pipeline identified other proteins that are potential serological biomarkers for colorectal cancer patients: a recent study by Yao and colleagues [28] identified EFEMP2 (EGF-containing fibulin-like extracellular matrix protein 2 or Fibulin 4) and thrombospondin 2 (THBS2) as a potential biomarkers detected in the serum of colorectal cancer patients. In accord with these data, we detected both EFEMP2 and THBS2 in both primary and secondary colon tumors but not in normal tissues.…”
Section: Resultsmentioning
confidence: 80%
“…drugs, cytokines, radioisotopes) that could be coupled, for example, to anti-disease-specific ECM protein antibodies, on the model of systems developed in the Neri lab [80, 81]. In addition, proteolytic fragments of ECM proteins can be released in body fluids and could be used as readouts for disease progression or treatment efficiency [82–84]. …”
Section: Introductionmentioning
confidence: 99%
“…CRC biomarkers can be detected through a differential proteomic analysis of blood. Serum biomarkers have been described and used for non-invasive testing to detect CRC [14,15]. Potential biomarkers have also been identified by evaluating CRC cell line-derived secretome [16].…”
Section: Introductionmentioning
confidence: 99%